1992
DOI: 10.1063/1.529660
|View full text |Cite
|
Sign up to set email alerts
|

Conformal invariance in a Dirac oscillator

Abstract: The conformal invariance properties of a Dirac oscillator are established. A set of operators is constructed whose algebra shows that it can be considered as a conformal system. The operators are then used to solve the problem using algebraic techniques. The superconformal generalization of the algebra is also worked out, and some consequences of these invariances for the properties of the model are mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…The interest in the problem was revived by Moshinsky and Szczepaniak [18], who gave it the name of DO because, in the nonrelativistic limit, it becomes a harmonic oscillator with a very strong spin-orbit coupling term. Physically, it can be shown that the DO interaction is a physical system, which can be interpreted as the interaction of the anomalous magnetic moment with a linear electric field [19,20]. The electromagnetic potential associated with the DO has been found by Benitez et al [21].…”
Section: Advances In High Energy Physicsmentioning
confidence: 99%
“…The interest in the problem was revived by Moshinsky and Szczepaniak [18], who gave it the name of DO because, in the nonrelativistic limit, it becomes a harmonic oscillator with a very strong spin-orbit coupling term. Physically, it can be shown that the DO interaction is a physical system, which can be interpreted as the interaction of the anomalous magnetic moment with a linear electric field [19,20]. The electromagnetic potential associated with the DO has been found by Benitez et al [21].…”
Section: Advances In High Energy Physicsmentioning
confidence: 99%
“…Another application for these models is in the study of the radial motion of test particle near the horizon of extremal Reissner-Nordström black holes [35,37]. Also, another interesting application of the superconformal symmetry is the treatment of the Dirac oscillator, in the context of the superconformal quantum mechanics [39][40][41][42]46].…”
Section: The Superconformal Quantum Mechanics From Wh Algebramentioning
confidence: 99%
“…Another application for these models is in the study of the radial motion of test particle near the horizon of extremal Reissner-Nordström black holes [6,7]. Also, another interesting application of the superconformal symmetry is the treatment of the Dirac oscillator [21,22].…”
Section: The Superconformal Quantum Mechanicsmentioning
confidence: 99%
“…We remark that since h,h and H 0 commute with each other, they form a set of mutually commuting operators. The superhamiltonian h andh are extensions of the ones in references [21,22] for the superconformal Dirac oscillator.…”
Section: The Superconformal Quantum Mechanicsmentioning
confidence: 99%